STILL BIRTH RATE IN DISTRICT HEAD QUARTER HOSPITAL ABBOTT AB AD - Shah, S. Humayun; Begum, Nazakat; Bano, Aniqa; Pervez, Shaheen; ullah, Rizwan (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: This retrospective study was done at District Headquarter Hospital, Abbottabad. The prevalence of still birth was studied among 853 infants born in maternity ward of DHQ Hospital, Abbottabad during two and a half years. The still birth rate observed was 112.5/1000. The rate was higher among multigravida and in females of more than 35 years’ age. The prominent etiological factors were multi-parity prolonged and obstructed labour and antepartum haemorrhag